Contextualization of Islamic Values through Local Wisdom: Study of the Values of Si Tou Timou Tumou Tou and Silih Asah Silih Asih Silih Asuh - Umar, Muhammad Faiz Ardafi; Mopoliu, Abdul Ziqron; Umar, Mardan; Fadlan, Aufa; Surahman, Cucu (IAIN Manado, 2025)
This research aims to analyze the contextualization of Islamic values through local wisdom in social interactions and educational environments. The implementation of cultural and religious values has become an important issue in multicultural societies, especially in countries with ethnic and cultural diversity, such as Indonesia. Therefore, universal Islamic values can provide strong moral guidance, while local wisdom can offer practical ways to implement them. This research uses a qualitative approach. The data collection techniques used in this research include: In-depth interviews to explore their views and experiences regarding the contextualization of Islamic values and local wisdom. Next, Observation by directly observing social and cultural practices in the community that reflect the integration of Islamic values with local wisdom and Documentation Study. The research results show that Islamic values are relevant to local wisdom values and have been implemented in daily life. The support of the government and society plays a crucial role in the contextualization of those values.